Intellectual trends and explanatory theory for occupational safety And prevention of work accidents - BenSaada, Hanane; Hadjadj, Ahmed (Social Empowerment Journal, 2021)
The human resource is the main engine of the production process in the various workplaces, and without the human element, devices, tools and huge machines will not achieve their role and will remain useless and do not work if the human mind that moves them, employs and preserves them is not available. Therefore, he must have safe working conditions to achieve the appropriate degree in his performance of work. Through our research paper, we seek to address the most important intellectual and theoretical trends to achieve occupational safety in industrial establishments and institutions using technical and technical means to prevent work accidents.